EFEKTIVITAS PEMUTAKHIRAN DATA PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN MIMIKA-PAPUA - Yahya Nusa (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2019)
The purpose of this study is to determine and analyze the effectiveness of updating the PBB-P2 data to the increase of PBB-P2 tax revenue, as well as to determine the contribution of PBB-P2 to the increase revenue from Regional Taxes (do you mean: Local government taxes) and Original Regional Revenues in Mimika Regency. (Do you mean: Local Government Original revenue). This research using descriptive analysis with a quantitative approach. Data Collected by observation, interview, documentation and literature review. To measure the effectiveness of PBB-P2 data updating on the increase of PBB-P2 tax revenue is analyzed by comparing realization of PBB-P2 before and after updating the PBB-P2 data. while to measure the contribution of PBB-P2 to the increase in revenue from Regional Tax and Regional Original Revenue in Mimika Regency (??) used contribution analysis. The results showed that after updating the data of PBB-P2, the average level of acceptance of PBB-P2 increased by 101.47%, with Very Effective criteria. While the average contribution of PBB-P2 to Regional Tax after updating the data is 16.73% with the criteria for Less and the average contribution of the PBB-P2 to the Original Local Revenue after updating the data is 10.34% with the criteria Less. This shows that the updating of PBB-P2 data did not make a significant contribution to Regional Taxes and Regional Original Revenues because the Realization of Regional Taxes and the realization of Regional Original Revenues were not followed by an increase in the realization of PBB-P2.